Experimentation on the impact of partial replacement of cement with glass powder in mortar mixture. (2022) - Gokulakannan, S.; Mukesh, P.; Anitha, M.; Arul Sri, SP.; Dinesh Kumar, G.; Vijayakumar, V.
Abstract: Millions of tons of discarded glass are produced worldwide each year. When glass is no longer usable, it is disposed of in landfills, which is not sustainable because glass does not degrade naturally. Silica makes up most of the glass. A significant step toward the creation of ecologically benign, economically sound, and energy-efficient infrastructure systems might be the use of powdered waste glass in mortar as a partial replacement for cement. It is anticipated that waste glass when powdered into tiny particles and combined with cement hydrates, will undergo pozzolanic reactions and produce secondary Calcium Silicate Hydrate (CSH). Both clear and colored glass chemical characteristics were examined in this study. Using the X-ray fluorescence (XRF) technology, chemical analyses of glass and cement samples revealed small changes in the composition of clear and colored glasses. Tests on mortar's flow and compressive strength were performed by adding 0–25 percent powdered glass while maintaining a constant water-binder-glass ratio across all replacement levels. Additional experiments were carried out with the same mix specifications with a dose of 1 % super plasticizing admixture (by weight of cement) to assess the packing and pozzolanic effects, and they typically revealed an improvement in compressive strength of mortars with admixture. Samples were made and evaluated for strength, much like with mortar cubes (until 1-year curing). The findings of the compressive strength test showed that recycled glass mortar provided more strength compared to control samples. It was determined that a 20 % substitution of waste glass for cement made financial and environmental sense. According to the results of the compressive strength test in the mortar at 90 & 365 days, the optimal glass content was found to be 20 %, with a compressive strength that was 8 % higher than the control mortar.